Вобраз селянша у паэмах Вшцэся Каратынскага i Я н к Лучыны (Тамта i Паляутчыя акварэлът з Палесся) - Wasiluk, Joanna (Acta Polono-Ruthenica, 2018)
The main heroes of Wincenty Korotyński and Janka Łuczyna’s works were simple people, peasants - authors and bearers of main national elements. Just these people spoke Belorussian, they cultivated customs and rituals of their ancestors. They used folk-wisdom in their everyday life. W. Korotyński in Tomiło aspired to show mentality of working people, who also deserved for better lot. J. Łuczyna in Akwarelki myśliwskie z Polesia showed positive image of Byelorussian people of decline of XIX century, determined national features of their character. Delving in a simple man’s soul, his internal world, saying about his experience, feelings and troubles the poet showed social and national problems in his works. Both writers were close to realistic showing the reality, but they showed different faces of byelorussian peasant in their works of the middle and end of XIX century.